Identificación de competencias: una estrategia para la formación en el Espacio Europeo de Educación Superior - Oliveros Martín-vares, Laura (Revista Complutense de Educación, 2006)
The European Higher Education Area brings some changes. Using competencies to describe educational outcomes is one of these. Competencies management has a long tradition at work organizations as a process that improves workers and organizations performance. The knowledge of this experience has provided can now be used to implement the main process –competencies identification, development, and evaluation– at university. However some changes must be done. The reasons for that are described and some solutions are suggested.